Ancient Water Technologies - Mays, L.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
There is no more fundamental resource than water. The basis of all life, water is fast becoming a key issue in today$1 (Bs world, as well as a source of conflict. This fascinating book, which sets out many of the ingenious methods by which ancient societies gathered, transported and stored water, is a timely publication as overextraction and profligacy threaten the existence of aquifers and watercourses that have supplied our needs for millennia. It provides an overview of the water technologies developed by a number of ancient civilizations, from those of Mesopotamia and the Indus valley to later societies such as the Mycenaeans, Minoans, Persians, and the ancient Egyptians. Of course, no book on ancient water technologies would be complete without discussing the engineering feats of the Romans and Greeks, yet as well as covering these key civilizations, it also examines how ancient American societies from the Hohokams to the Mayans and Incas husbanded their water supplies. This unusually wide-ranging text could offer today$1 (Bs parched world some solutions to the impending crisis in our water supply.s
A Brief History of Water Technology During Antiquity: Before the Romans -- Water Technology in Ancient Mesopotamia -- Water Technology in Ancient Egypt -- Ancient Greek Lavatories: Operation with Reused Water -- Water Resource Management for Iran$1 (Bs Persepolis Complex -- A Web Based Information System for the Inspection of the Hydraulic Works in Ancient Greece -- A Brief History of Roman Water Technology -- Analysis of the Water System of the Ancient Roman City of Apamea -- Water Technology in the Ancient American Societies -- Ground Water Resources and Earthquake Hazards: Ancient and Modern Perspectives -- Lessons from the Ancients on Water Resources Sustainability.s
Keywords: Environmental sciences; Science -- History; Environmental pollution; Archaeology; Environment; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Archaeology; History of Science